177k views
5 votes
If f (x) = square root of x + 12 g(x) = 2 square root x, what is the value of (f – g)(144)?

–84
–60
0
48

User Shurmajee
by
6.1k points

2 Answers

4 votes

Answer:

o is correct answer

Explanation:

f(x)=
√(x)+12

g(x)=2
√(x)

we will find

(f-g)x=
√(x)+12-2
√(x)

(f-g)x=-
√(x)+12

now we will find

(f-g)(144)

put x=144

(f-g)(144)=-
√(144)+12

(f-g)(144)=-12+12=0

hence proved


User Andrew Hanson
by
6.0k points
4 votes

Answer:

0

Explanation:


f(x)=√(x)+12  and g(x)=2√(x)

We need to find (f-g)(144)

(f-g)(144) = f(144) - g(144)


f(x)=√(x)+12


f(144)=√(144)+12=12+12= 24


g(x)=2√(x)


g(144)=2√(144)=2(12)= 24

(f-g)(144) = f(144) - g(144)= 24-24=0

User Matias Pequeno
by
6.1k points